Pengaruh Index Card Match Berbantuan Flash Card Terhadap Hasil Belajar Bahasa Indonesia SD Gugus III Bengkulu - Mulyani, Tri; Yuliantini, Nani; Yusnia (Universitas Bengkulu, 2024)
his study aims to determine the effect of using the Index Card Match learning model assisted by Flash Cards on grade IV Indonesian language learning outcomes in SD Negeri Gugus III Bengkulu city. This research is a type of quantitative research with the research method, namely the Quasi Experiment method with the research design The Matching Only Pretest-Posttest Control Group Design. The population in this study were 4th grade students of SD Negeri Gugus III Bengkulu City. The research sample was taken using random sampling technique, obtained fourth grade students of SD Negeri 57 Bengkulu City as the experimental group and fourth grade students of SD Negeri 48 Bengkulu City as the control group. The instrument used was a multiple choice test sheet totaling 10 questions. Implementation of the test twice, namely before and after learning takes place in the experimental class and control class. From the results of the t-test calculation of students' posttest scores, sig (2-tailed) 0.002 is smaller than 0.05. It shows that there is a difference in posttest results between the experimental class and the control class due to the treatment of the two different classes. So it can be concluded that there is an effect of using the Index Card Match learning model assisted by Flash Cards on the learning outcomes of Indonesian language class IV in SD Negeri Gugus III Bengkulu City.